Kriminologis Tindak Pidana Penyalahgunaan Narkotika Anak - Sujud, Muhammad Satrio; Titahelu, Juanrico Alfaromona Sumarezs; Saimima, Judy Marria (Faculty of Law Universitas Pattimura, 2025)
This study aims to realize the criminological review of drug abuse crimes committed by children in Ambon City by analyzing the events that caused the occurrence of drug abuse crimes by children in Ambon City and the efforts made by Polresta P. Ambon and P. P. Lease in overcoming and following up on the occurrence of drug abuse crimes by children in Ambon City. This study is an empirical legal study with descriptive analysis. The data for this study were obtained from primary data and secondary data. Based on the results of the study and discussion, it can be concluded that there are several factors that influence drug abuse in Ambon: personal factors, education, family, economy, and environment. Among the five factors, family factors are known to be the most influential factor in drug abuse in Ambon City. In addition, children need special attention from environmental aspects related to their relationships with their peers and the people around them. This effort requires the role of parents to supervise and protect their children so that they do not fall into the influence of friends who invite them to try narcotics for the first time by giving them for free, after the victim is addicted, the drugs will be sold to the child because they are already addicted. Meanwhile, efforts made by the P. Ambon and P. P. Lease Police in dealing with drug abuse by children are carried out in several ways, namely by providing guidance, advice and education about the dangers of drug abuse through e-brochures, posters and infographics and working together with all authorities, the community, religious leaders and the local government to help combat drugs in Ambon City.